CLINICAL MANIFESTATIONS OF METABOLIC CHANGES IN HYPOTHYROIDISM AND HYPERTHYROIDISM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Thyroid hormones exert profound regulatory effects on systemic metabolism, with deviations in their secretion precipitating distinctive metabolic phenotypes. This review examines the clinical and biochemical manifestations arising from metabolic alterations in hypothyroidism and hyperthyroidism. Through comparative analysis of carbohydrate, lipid, and protein metabolism alongside energy homeostasis, cardiovascular implications, and diagnostic markers, this work elucidates the pathophysiological mechanisms underlying thyroid-mediated metabolic dysfunction and emphasizes the clinical imperative for early recognition and therapeutic intervention.